K3 FREQUENCY VALUE ANALYSIS IN A HIGH-RISE BUILDING - Mohamad Sobirin, Krishna Mochtar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Construction projects are jobs that have a high risk of work accidents with the possibility of serious work accidents. The risk of accidents is higher in developing countries where the workforce used in educational backgrounds is relatively low. Related to this condition, King and Hudson (1985).Determination of the frequency of frequency or frequency of the occurrence of K3 Construction Risk to multi-storey buildings, has different values such as rarely, sometimes and often, in accordance with the regulations of the Ministry of Public Works Number: 05 / PRT / M / 2014. i.e. the value = 1 is rare in construction activities,Value 2= Sometimes occurs in construction activities and value = 3 Often occurs in constructal activities. limit the frequency value of the occurrence of the type of risk of K3 construction. In this study, using fuzzy logic mamdani method. To get the output of this method requires 4 stages, namely; 1) The formation of fuzzy sets; 2) Application of implication function; 3) Composition of rules; 4) Defuzzification, from the results of defuzzifikas Based on the results of the study can be collected additional values for the limit of the value of K3 frequency, namely; Frequency Value Limit for "Rare" between 0-2, "Sometimes" between 3-5 while for "Often" is 6-8